Postoperative Analgesia after Low-Frequency Electroacupuncture as Adjunctive Treatment in Inguinal Hernia Surgery with Abdominal Wall Mesh Reconstruction. Issue 5 (October 2015) - Dalamagka, Maria; Mavrommatis, Christos; Grosomanidis, Vassilios; Karakoulas, Konstantinos; Vasilakos, Dimitrios; Samara, Maria; Saros, Christos; Crommydas, George
Objective: To determine whether an electroacupuncture (EA) technique that was developed for a surgical population under general anaesthesia reduces pain after mesh inguinal hernia open repair. Methods: A total of 54 patients with right or left inguinal hernia were randomised to group I (preoperative, intraoperative, postoperative EA), group II (preoperative, postoperative EA), or a sham control group (group III; preoperative and postoperative placement of needles, but without skin penetration). The Visual Analogue Scale (VAS) (primary outcome) and the State-Trait Anxiety Spielberger Inventory were evaluated preoperatively and at 30 min, 90 min, 10 h and 24 h after surgery. Pain threshold and tolerance were evaluated using an algometer at these same time points and preoperatively before and after EA. Levels of the stress hormones cortisol, corticotrophin and prolactin were determined at 30 min, 90 min and 10 h after surgery and preoperatively before and after EA. Results: The results showed significant differences between the true EA and control groups. The true EA groups (I and II) showed statistically significantly greater improvements in the primary (VAS pain, p<0.05) and secondary outcome measures (Anxiety scale; algometer measurements, p<0.05 and stress hormones, p<0.01) compared to the control group. There were no statistically significant differences between groups I and II. Conclusions: Electroacupuncture reduces postoperative pain after mesh inguinal hernia repair and decreases stress hormone levels and anxiety during the postoperative period. Trial Registration Number: ClinicalTrials.gov identifier NCT01722253.